Clinical outcomes of intermittent panitumumab based-therapy for previously treated older patient with metastatic colorectal cancer: a case report and review of literature - Rosati, Gerardo; Annunziata, Luigi; Scarano, Enrico; Dapoto, Francesca; Bilancia, Domenico (Frontiers in Oncology, 2024)
Background Metastatic colorectal cancer is one of the most common causes of cancer death worldwide, and its incidence increases with age. Treating an older RAS and BRAF wild-type patient represents a challenge for the medical oncologist, even more so for those patients defined as “vulnerable” and undergoing at least two lines of therapy. In this context, recent evidence supports the role of retreatment with anti-EGFR inhibitors and the use of liquid biopsy. However, frequent skin toxicity constitutes a limitation of therapy, especially in older people. Since it has been described that continuous administration of these monoclonal antibodies leads to acquired resistance to anti-EGFRs, with consequent therapeutic failure, an intermittent strategy with chemotherapy plus an anti-EGFR could help maintain the efficacy of the treatment over time, delaying the resistance and improving patients’ quality of life. Case presentation In this case report, we describe the case of an older RAS and BRAF wild-type patient reporting a clinical response after first-line chemotherapy with FOLFOX + panitumumab, subsequently interrupted in the absence of disease progression. After radiological worsening and two additional lines of therapy, the reintroduction of panitumumab plus 5-fluorouracil, administered with a stop-and-go strategy, allowed the patient to benefit from the same drugs for 2 years from diagnosis, to achieve a clinical response during fourth-line treatment lasting more than 3 years, to delay resistance and to avoid unacceptable anti-EGFR skin toxicity. This patient, who died from a myocardial infarction more than 5 years after diagnosis, represents the case of a good synergy between molecular profile of disease and reintroduction of an anti-EGFR with intermittent strategy.